2021
DOI: 10.1097/iae.0000000000003050
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Endophthalmitis on Recurrence of Macular Edema in Eyes Receiving Intravitreal Anti–vascular Endothelial Growth Factor

Abstract: Purpose: Visual outcomes after postinjection endophthalmitis have been well-studied, but the effect of endophthalmitis on the underlying exudative disease process remains unclear. We investigate the need for continued anti-vascular endothelial growth factor injections after endophthalmitis.Methods: Eyes that developed endophthalmitis after intravitreal injection of antivascular endothelial growth factor between January 1, 2016, and May 31, 2018, at a single academic retina practice were identified. Retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
3
1
0
Order By: Relevance
“…The OCT results of eyes filled with silicone oil in our case series showed disruption of the inner retinal layers but stabilization of the retina in regard to changes related to wet age-related macular degeneration (AMD). This is consistent with the results obtained recently by Uhr et al [ 29 ]. They concluded that endophthalmitis after anti-VEGF injection was associated with the relative stability of the underlying exudation.…”
Section: Discussionsupporting
confidence: 94%
“…The OCT results of eyes filled with silicone oil in our case series showed disruption of the inner retinal layers but stabilization of the retina in regard to changes related to wet age-related macular degeneration (AMD). This is consistent with the results obtained recently by Uhr et al [ 29 ]. They concluded that endophthalmitis after anti-VEGF injection was associated with the relative stability of the underlying exudation.…”
Section: Discussionsupporting
confidence: 94%
“…This in part is explained by sequelae, such as postvitrectomy cataract formation in phakic individuals and relapse of disease such as macular pathology in postinjection subjects. 13,14 Overall, visual acuity improvement is observed with respect to the median presenting visual acuity of HM and this is consistent with other studies, which show visual acuity improvement following treatment. 7,15,16 One hundred and fifty-nine patients had resultant SVL, as influenced by poor presenting visual acuity, culture positivity and absence of the red reflexthe latter being regarded as a clinical indicator of severity.…”
Section: Discussionsupporting
confidence: 89%
“…This in part is explained by sequelae, such as post‐vitrectomy cataract formation in phakic individuals and relapse of disease such as macular pathology in post‐injection subjects 13,14 . Overall, visual acuity improvement is observed with respect to the median presenting visual acuity of HM and this is consistent with other studies, which show visual acuity improvement following treatment 7,15,16 .…”
Section: Discussionsupporting
confidence: 88%
“…After successful management of IRE in patients with AMD, studies report potential reductions in activity of the exudative disease process. In a retrospective report, 14% of eyes had no fluid recurrence post-endophthalmitis and 48% achieved a greater than 12-week recurrence free interval (as opposed to only 8.3% prior to endophthalmitis) [ 131 ]. In a case series of 7 AMD patients, Kokame et al reported that 5 of 7 had resolution of subretinal and sub-RPE fluid without the need for additional anti-VEGF injections post-infection [ 132 ].…”
Section: Resultsmentioning
confidence: 99%